Molecular findings from influenza A(H1N1)pdm09 detected in patients from a Brazilian equatorial region during the pandemic period - Maria José Couto Oliveira; Fernando do Couto Motta; Marilda M Siqueira; Paola Cristina Resende; Priscilla da Silva Born; Thiago Moreno L Souza; Milene Mesquita; Maria de Lourdes Aguiar Oliveira; Sharon Carney; Wyller Alencar de Mello; Vera Magalhães (Memorias do Instituto Oswaldo Cruz, 2014)
After the World Health Organization officially declared the end of the first pandemic of the XXI century in August 2010, the influenza A(H1N1)pdm09 virus has been disseminated in the human population. In spite of its sustained circulation, very little on phylogenetic data or oseltamivir (OST) resistance is available for the virus in equatorial regions of South America. In order to shed more light on this topic, we analysed the haemagglutinin (HA) and neuraminidase (NA) genes of influenza A(H1N1)pdm09 positive samples collected during the pandemic period in the Pernambuco (PE), a northeastern Brazilian state. Complete HA sequences were compared and amino acid changes were related to clinical outcome. In addition, the H275Y substitution in NA, associated with OST resistance, was investigated by pyrosequencing. Samples from PE were grouped in phylogenetic clades 6 and 7, being clustered together with sequences from South and Southeast Brazil. The D222N/G HA gene mutation, associated with severity, was found in one deceased patient that was pregnant. Additionally, the HA mutation K308E, which appeared in Brazil in 2010 and was only detected worldwide the following year, was identified in samples from hospitalised cases. The resistance marker H275Y was not identified in samples tested. However, broader studies are needed to establish the real frequency of resistance in this Brazilian region.